Monitoring of potential contaminants in beer from the Czech Republic - Olšovská, Jana; Jandovská, Vladimíra; Běláková, Sylvie; Kubizniaková, Petra; Vrzal, Tomáš; Štěrba, Karel (KVASNY PRUMYSL, 2019)
The health safety of beer is still a discussed topic. In the Czech Republic, there is a well-developed system for controlling the content of potential beer contaminants, which are regularly attended by a number of large and medium-sized breweries and are organized by laboratories of the Research Institute of Brewing and Malting. For many years aliphatic chlorinated hydrocarbons, biogenic amines, nitrates, phthalates, ATNC, nitrosamines, polychlorinated biphenyls, polycyclic aromatic hydrocarbons, heavy metals, mycotoxins, coliforms, and recently pesticides in beer have been analyzed. This study summarizes five-year results and extends information about the origin, health risks and hygiene limits of controlled substances and bacteria in beer. The study proves that the level of health safety of beers in the Czech Republic is very high, which is closely related to the high hygiene level of controlled breweries. The number of positive samples was only minor, 8 positive samples were found in 220 beer samples controlled for 44 chemical contaminants. Three positive samples contaminated by coliform bacteria were found among 675 controlled ones.